Identification of zoonotic parasites in the musculature and visceral cavity of Hoplias malabaricus Bloch 1794 “fasaco” (Characiformes: Erythrinidae) from the Belén market, Iquitos-Peru - Pasquel Pinedo, Carmen Patricia (2022)
The aim of this study was to identify zoonotic parasites in the musculature and visceral cavity of Hoplias malabaricus "fasaco" from the Belén market in Iquitos, Peru. The visceral cavity was reviewed through a longitudinal cut from the opening of the anus to the height of the gills. Besides, fine cuts were made in the musculature of the fish to detect encysted or free parasites. Nematodes were clarified using lactic acid, Hoyer's medium was used for pentastomids, and trematodes were stained with Langeron's alcoholic carmine. The presence of zoonotic endoparasites was observed: L3 larvae of the nematode Eustrongylides sp Jagerskiold, 1909 (Dioctophymatidae), the trematode Ithyoclinostomum dimorphum Witenberg, 1925 (Clinostomidae) and the pentastomid Sebekia sp.